Impacts of ESG practices on the operation performance: An empirical study of Vietnamese commercial banks - PHAM, Ngoc Thi Kim; NGUYEN, Dan Thi Thanh (International Journal of Innovative Research and Scientific Studies, 2025)
Environmental, Social, and Governance (ESG) activities are becoming essential drivers of performance for commercial banks in Vietnam. This study aims to identify the impact of ESG practices on the financial success of 27 Vietnamese banks from 2015 to 2023 and offers actionable insights for policymakers and bank leaders. We evaluate bank performance using key indicators such as Return on Assets (ROA) and Return on Equity (ROE), alongside moderating variables like size (SIZE), capital adequacy (CAP), cost-to-income ratio (CIR), and loan-to-deposit ratio (LDR). Additionally, we consider macroeconomic factors, including per capita income (GDP), inflation (INF), and the impact of COVID-19. Our research sample is selected based on adherence to the Global Reporting Initiative (GRI) Standards, ensuring a solid approach to ESG reporting. Employing STATA17 software and advanced models, our findings reveal that banks with robust ESG practices, particularly in social and governance areas, achieve significantly higher ROA and ROE. This underscores that investing in ESG is not merely a regulatory obligation but a strategic advantage that enhances long-term financial performance and competitiveness. Increasing awareness of sustainable development in bank management, developing a long-term strategy for ESG Standards, and enhancing transparency in ESG disclosures are essential recommendations for ESG practices for Vietnamese commercial banks to strengthen their performance in a sustainable way.